2001
DOI: 10.1055/s-2001-14334
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Various Piper methysticum Cultivars with CNS Receptors in vitro

Abstract: Methanolic leaf and root extracts of the Hawaiian kava (Piper methysticum Forst.) cultivars, Mahakea, Nene, Purple Moi and PNG, were tested on binding affinities to CNS receptors including GABAA (GABA and benzodiazepine binding site), dopamine D2, opioid (mu and delta), serotonin (5-HT6 and 5-HT7) and histamine (H1 and H2). HPLC analysis was carried out in order to determine the amount of the main kavalactones kavain, 7,8-dihydrokavain, methysticin, 7,8-dihydromethysticin, yangonin and 5,6-demethoxyyangonin. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 0 publications
2
29
0
Order By: Relevance
“…For example, synthetic as well as herbal 5-HT 3 antagonists like Zingiber officinale can also exert anxiolytic effects without interfering with the performance on learning tasks (Buhot et al, 2000;Hasenöhrl et al, 1998). This is interesting in the light of recent evidence showing that kavapyrones can directly interact with central 5-HT receptive sites (Dinh et al, 2001;Grunze et al, 2001), which are considered to play a crucial role in the neural control of emotion and associative processes (Meneses, 1999).…”
Section: Discussionmentioning
confidence: 95%
“…For example, synthetic as well as herbal 5-HT 3 antagonists like Zingiber officinale can also exert anxiolytic effects without interfering with the performance on learning tasks (Buhot et al, 2000;Hasenöhrl et al, 1998). This is interesting in the light of recent evidence showing that kavapyrones can directly interact with central 5-HT receptive sites (Dinh et al, 2001;Grunze et al, 2001), which are considered to play a crucial role in the neural control of emotion and associative processes (Meneses, 1999).…”
Section: Discussionmentioning
confidence: 95%
“…Kava's anticonvulsant properties have been linked to its interaction with the voltage-gated sodium and calcium channels (Gleitz et al 1996;Maura et al 1997;Friese and Gleitz 1998;Schirrmacher et al 1999). Kava's anxiety-reducing effects have been suggested to be due to its interactions with the GABA A receptor; however, data supporting this conjecture are equivocal (Davies et al 1992;Jussofie et al 1994;Boonen and Häberlein 1998;Dinh et al 2001). Other studies have indicated that kava extracts and kava lactones may alter several neurochemical systems (Seitz et al 1997;Baum et al 1998;Feger et al 1998;Dinh et al 2001); however, none of these actions have been associated with specific behavioral effects in vivo.…”
Section: Introductionmentioning
confidence: 91%
“…These kavalactones include desmethoxyyangonin (DMY), dihydrokawain, dihydromethysticin (DMS), kawain, methysticin, and yangonin. The relative abundance of the kavalactones varies markedly among different parts of the plant and also depends on where the plant grows (Singh and Blumenthal, 1997;Dinh et al, 2001). Structurally, the active kavalactones exist as the (ϩ) isomer, and all kavalactones contain a benzene ring and a methoxy lactone connected via an ethyl or ethylene bridge (Dharmaratne et al, 2002).…”
mentioning
confidence: 99%